Nutritional Long-Term Complications After MBS and Solutions - BATAR, NAZLI (My University, 2019)
Although bariatric surgery positively affects the general health status of the obese individual, it may make the individual susceptible to serious nutritional deficiencies. Inadequate energy intake after surgery, rapid weight loss, food intolerance, lack of nutritional support or prolonged vomiting, etc. nutritional deficiencies may develop. The pathophysiology of nutritional deficiencies resulting from bariatric surgery is multifactorial. The severity o f these deficiencies depends on the preferred surgical technique. Postoperative protein, minerals, especially iron and calcium and some vitamins (vitamin B l2, vitamin D, folic acid and vitamin B l) are inadequate. In the postoperative period, protein consumption of the patients may be insufficient. Intolerance to protein foods may be encountered. Protein malnutrition is the most serious macronutrient complication after bariatric surgery; regular protein intake and monitoring and evaluation of the patient's nutritional status is very important. Dietitians should use all evaluation criteria (biochemical tests, anthropometric measurements, functional capacity, etc.) to identify, monitor and treat protein malnutrition. Fast and excessive nutrition may cause edema, hypokalemia, hypophosphatemia and hypomagnesemia with refeeding syndrome. In general, protein intake in patients after bariatric surgery is recommended as 60-120 g per day. According to ASMBS principles, 60-90 g protein is recommended for patients after RYGB, and 90-120 g protein for BPD or BPD / DS patient. Patients may have difficulty in reaching postoperative protein intake targets early in the postoperative period due to gastric volume, or they may have intolerance to protein foods in the early period, but patients should be encouraged by their dieticians for protein intake targets.

Bariatrik cerrahi, obez bireyin genel sağlık durumunu olumlu etkilese de bireyi ciddi beslenme yetersizliklerine açık hale getirebilir. Ameliyattan sonra yetersiz enerji alımı, hızlı ağırlık kaybı, gıda intoleransı, beslenme desteğinin eksikliği veya uzun süren kusma şikayetleri vb. nedeniyle beslenme yetersizlikleri gelişebilmektedir. Bariatrik cerrahiden kaynaklanan beslenme yetersizliklerinin patofizyolojisi çok yönlüdür. Bu eksikliklerin şiddeti tercih edilen cerrahi tekniğe bağlıdır. Ameliyat soması protein, minerallerden özellikle demir ve kalsiyum ve bazı vitaminlerde (B12 vitamini, D vitamini, folik asit ve B[ vitamini) yetersizliklere rastlanılmaktadır. Postoperatif süreçte hastaların proteinli besin tüketimi yetersiz olabilmektedir. Proteinli besinlere karşı intolerans ile karşılaşılabilir. Protein malnütrisyonu, bariatrik cerrahi soması en ciddi makro besin komplikasyonudur; düzenli protein alımı ve hastanın beslenme durumunun izlenmesi ve değerlendirilmesi çok önemlidir. Diyetisyenler, protein malnutrisyonunu belirlemek, izlemek ve tedavi etmek için tüm değerlendirme kriterlerini (biyokimyasal testler, antropometrik ölçümler, fonksiyonel kapasite...vb) kullanmalıdır. Hızlı ve aşırı besleme ödem, hipokalemi, hipofosfatemi ve hipomagnezemi belirtileri ve semptomları ile kendini gösteren refeeding sendromununa neden olabilir. Genel olarak, bariatrik cerrahi sonrası hastalarda protein alımı günde 60-120 g olarak önerilmiştir. ASMBS ilkelere göre, RYGB sonrası hasta için 60-90 g protein, BPD veya BPD / DS hasta için 90-120 g protein önerilmektedir. Hastaların ameliyat soması protein alım hedeflerine, ameliyat soması erken dönemlerde ulaşmaları gastrik hacim nedeniyle zor olabilir veya erken dönemde proteinli besinlere karşı intoleransları olabilir yine de hastalar, protein alım hedefleri için diyetisyenleri tarafından teşvik edilmelidir.
MBC Sonrası Beslenmeye Bağlı Uzun Dönem Komplikasyonlar ve Çözümleri
Keywords: Beslenme; Yiyecek ve İçecek; Obezite Yönetimi; Kalori Ölçümü; Nutrition; Food and Drink; Obesity Management; Calorie Measurement